Analisis Kepemimpinan Manajerial Kepala Paud Fajar Berkah Bagik Lonjer Desa Rensing Kec. Sakra Barat - Anwar, Muhammad (FAKULTAS TARBIYAH, 2020)
This study aims to describe and analyze the managerial leadership of the Head of Early Childhood Education (PAUD) Fajar Berkah Bagik Lonjer. The focus of the research is the managerial leadership of the PAUD Fajar Berkah Bagik Lonjer head of Rensing Village with the sub-focus of the research: (1) Leadership concept skills of Fajar Berkah Bagik Lonjer PAUD Rensing Village. (2) Human skills (human skills). The data analysis technique uses an interactive pattern of Miles and Huberman data. The results obtained are (1) the Head of PAUD Fajar Berkah Bagik Lonjer in Rensing Village already has the ability to analyze a problem or problem, already has the ability to think rationally in every action, has the ability to be expert and proficient in various kinds of conceptions, and the Head of PAUD Fajar Berkah Bagik Lonjer, Rensing Village, has carried out planned observations of management activities. (2) The head of PAUD Fajar Berkah Bagik Lonjer in Rensing Village in carrying out his duties has met expectations to understand the behavior of teachers and students, understand the hearts, attitudes, and motives of teachers and students, communicate clearly and effectively to teachers and students, and has as expected to create effective, cooperative, practical, and diplomatic cooperation.